3, 3′‐[(1RS, 3SR)‐2‐Oxocyclohexane‐1, 3‐diyl]bis[(3RS, 3′SR)‐3‐hydroxyindolin‐2‐one] dihydrate: organic layers of R22(8), R22(16) and R66(40) rings linked by tetrameric water aggregates. (24th September 2013) - Becerra, Diana; Insuasty, Braulio; Cobo, Justo; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> The organic component of the title compound, C22H20N2O5·2H2O, exhibits approximate but noncrystallographic mirror symmetry. The molecules of the organic component are linked by a combination of one O—H...O hydrogen bond and two N—H...O hydrogen bonds to form sheets containing R22(8), R22(16) and R66(40) rings. These sheets are linked into a continuous three‐dimensional framework structure by cyclic centrosymmetric R42(8) water tetramers. Comparisons are made with some simpler analogues.